Acceptability and Antioxidant Activity Level of Shredded Banana Flower-Chicken Meat - Novidiyanto Novidiyanto; Ori Pertami Enardi; Ade Devriany; Auronita Puspa Pratiwi; Musrifa Airuni (Amerta Nutrition, 2020)
Background: Data Riskesdas 2013 shows that the average amount portion of vegetable consumption in people aged 10 years or older is only 0.5 portions while the vegetable consumption category is said to be "sufficient" is at least 5 portions per day for 7 days a week. Banana blossom is a vegetable and commonly found in Bangka Belitung Islands Province. Banana blossom processing as a source of vegetables rich in antioxidant compounds and chicken meat as a source of animal protein, needs to be done by processing into shredded banana blossom-chicken meat.Objectives: To determine the acceptability and antioxidant activity level of shredded banana blossom-chicken meat.Methods: This research is true experimental. Shredded banana blossom-chicken meat, made using 3 treatment, banana blossom 75%:chicken meat 25% (F1), banana blossom 50%: chicken meat 50% (F2), and banana blossom 25%:chicken meat 75% (F3). Furthermore, the acceptance of taste, colour, aroma, texture, overall, and antioxidant activity level of shredded banana blossom-chicken meat. Results: There was a significant difference in the acceptance of the colours of shredded F1, F2 and F3 (p = 0,00), while aroma, taste, texture and overall of the shredded F1, F2 and F3 were not significant (p> 0.05). Shredded F3 (banana blossom 25%: chicken meat 75%) is most preferred based on the parameters of colour, aroma, taste, texture and overall, and has the highest antioxidant activity value are 53.74%.Conclusions: Shredded banana blossom-chicken meat has a good acceptability and has a high antioxidant activity level.[AN1]